Reorganization Realities, Methodological Realities, and the Paradigm Dominance Game - Lynn M. LoPucki (Washington University Law Quarterly, 1994)
The comments I present here pertain to two subjects. The first is the Warren and Westbrook attack on "arm chair theorists' and the response of the Conferees to this attack. The second is the problem of sample selection and its relationship to regularized data gathering.
Keywords: Bankruptcy reorganization; United States; Corporate reorganizations; Social sciences